OPTIMIZATION OF MAGELANG POLICE SATPAS IN DRIVING LICENSE SERVICES TO IMPROVE PRIMARY SERVICE IN THE MAGELANG POLICE AREA - Taufik Hidayat (Police Studies Review, 2022)
ABSTRACT OPTIMIZATION OF MAGELANG POLICE SATPAS IN DRIVING LICENSE SERVICES TO IMPROVE PRIMARY SERVICE IN THE MAGELANG POLICE AREA Taufik Hidayat, 18.211, ahmadfarhan.th@gmail.com The focus of this Final Project research is motivated by the state of the covid-19 pandemic. The Magelang Police have started to make adjustments to the pandemic conditions. The adjustment is in the form of creating a special website in providing driving license services to the public. This website is called "polresmagelang.id". However, in its implementation it has not run optimally. So that in this final project, a study entitled "Optimization of the Magelang Police Satpas in Driving License Services in Improving Excellent Service is made". In this study using qualitative methods and using descriptive analysis type of research. The theories and concepts used in the preparation of this Final Project are management theory and swot theory to analyze problems in Optimizing Driver's License Services during a pandemic. Also, the concept of excellent service and the concept of public service as the basis for an appropriate service mechanism. The results of this study are obstacles in the implementation of SIM issuance in terms of personnel who have not followed the Dikjur, inadequate infrastructure, and the implementation is still far from the SOP for SIM services as stated in Perkap Number 9 of 2012 concerning Driving Permits. The Optimization of Satpas in Improving Excellent Service in the Magelang Police Area by using IT-based service innovations, namely Polres Magelang.id Keywords: Optimization, SIM Administration Unit, Service Improvement, Excellent Service.